KRISIS EKONOMI IRLANDIA TAHUN 2008-2012 - Utama, Aulia Adi; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research narrate about the economic crisis in Ireland. The discussion in thisstudy focused on the dimensions of the economic crisis in Ireland and the Irishgovernment's efforts to get out of the economic crisis since 2008. Ireland hit bythe crisis as a result of the domino effect of the economic crisis in Greece. Thedomino effect does not only stop in Greece, but also affected the countries ofPortugal, Italy, and Spain. Krsis core of the European economy hit region is thestate's inability to pay its debts. Irish government seeks to make foreign policy, inorder to strengthen the economy so they can get out of the crisis. Requestedassistance from the EU bailout fund and the IMF is the path of the Irishgovernment to get out of the economic crisis.Key words : Economic Crisis, Domino Effect, Uni Europe, IMF.